Business Strategy Formulation for Art Merchandise Brand (Case Study: Gutsy Prune) - Natalie Amadea; Mustika Sufiati Purwanegara (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
A part of Indonesia's creative industries is the art merchandise industry which is dominated by independent visual artists who establish their art merchandise brands to market original art merchandise. Visual artists try to apply the principles of entrepreneurship in their practice since entrepreneurship has a fundamental role in their artistic careers. A business strategy is needed for any art merchandise brand. To develop a business strategy that is based on the empirical case, an Indonesian art merchandise brand called Gutsy Prune is analyzed as a case study. Gutsy Prune needs to develop a business strategy to boost the sales stagnation and to ensure the business continuity within the art merchandise market. The methodology for the research is a qualitative method and it is executed by conducting in-depth interviews with Gutsy Prune's potential and current customers. The results from the interview will be treated as the primary data along with observation and competitor analysis, while information from literature research will be used as secondary data to support the primary data. The focus of the research is the formulation of a business strategy for the art merchandise brand and the data collection was conducted by using interviews, observation, competitor analysis, and literature research. Gutsy prune needs to have a business strategy to tackle the sales stagnation that is caused by the low rate of inventory turnover. Before formulating a business strategy to boost sales stagnation, a series of analysis that includes environmental scanning and customer analysis is performed. The result from the aforementioned analysis is further examined by using SWOT Analysis to discover the root causes of the sales stagnation. It has been concluded that Gutsy Prune possesses some weaknesses in its segmentation, targeting, positioning, value proposition, marketing mix, and organizational structure. To resolve the root causes, Gutsy Prune develops a business strategy that contains STP Strategy, Value Proposition Canvas, Marketing Mix Strategy, organizational structure design, and a generic competitive strategy to sums up the business strategy's direction. From the research, Gutsy Prune can establish a one-year implementation plan to execute the business strategy.